Decision Support System for Selection of Herbal Medicines for Diet Using the Simple Multi Attribute Rating Technique (SMART) Method: Dewi Wahyuni - Dewi Wahyuni (INFOKUM, 2020)
The circulation of drugs for the body's diet program process, is very much, be it chemical diet drugs, or herbal drugs. Chemical drugs are very much in demand by everyone, because the process is very fast, without thinking about the side effects they cause. As a result of consuming these chemical drugs can cause the immune system to become weak, slow down the body's metabolism, can be poisoned, can even result in death, while those who consume herbal medicines are very few, because the reactions in the process are so slow, and take a long time. For this reason, the author wants to conclude how to choose the right diet medicine for a healthy body diet (Syamsuni, 2006). Based on the problems and descriptions in the diet program above, the Simple Multi Attribute Rating Technique (SMART) method is used to assist the process of selecting the right herbal medicine. This method was chosen because it has a way to overcome problems in selecting herbal medicines for the right diet, so that the results given are more accurate. Thus, it can provide a positive response for every consumer in consuming herbal medicines to meet the dietary needs of their lives.